2020
DOI: 10.1021/acs.orglett.0c03226
|View full text |Cite
|
Sign up to set email alerts
|

Scalable Synthesis of Vicinal Quaternary Stereocenters via the Solid-State Photodecarbonylation of a Crystalline Hexasubstituted Ketone

Abstract: We report the synthesis and stereospecific solid-state photodecarbonylation of a hexasubstituted ketone featuring six distinct α-substituents. The photoproduct of the solid-state transformation features vicinal all-carbon quaternary stereocenters. While reactions carried out in bulk powders and aqueous crystalline suspensions were complicated by secondary photochemistry of the primary photoproduct, optimal conditions provided good yields and recyclable starting material. Subsequent transformations of the α-sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…This was overcome by irradiating the pyrazolines as aqueous nanocrystalline suspensions (Figure ). Our group has previously demonstrated that irradiating organic crystals prepared in this manner greatly minimizes optical issues associated with irradiation of dry powders. These suspensions can also be run through flow reactors, allowing for irradiation of crystalline material on scales as large as 25 g. Solid-state photodenitrogenations of pyrazolines 4c , 4h , and 4i were carried out under such conditions to high conversions (>90%) on scales as large as 1.2 mmol. The stereoselectivities for the corresponding cyclopropanes 5c , 5h , and 5i observed in these reactions were comparable to the results from the bulk-powder irradiations, and the yields improved when compared to their solution-phase counterparts. , These results demonstrate that the preparation and subsequent irradiation of suspended crystalline samples is an effective method to carry out highly selective solid-state photochemical reactions on synthetically useful scales.…”
Section: Resultsmentioning
confidence: 99%
“…This was overcome by irradiating the pyrazolines as aqueous nanocrystalline suspensions (Figure ). Our group has previously demonstrated that irradiating organic crystals prepared in this manner greatly minimizes optical issues associated with irradiation of dry powders. These suspensions can also be run through flow reactors, allowing for irradiation of crystalline material on scales as large as 25 g. Solid-state photodenitrogenations of pyrazolines 4c , 4h , and 4i were carried out under such conditions to high conversions (>90%) on scales as large as 1.2 mmol. The stereoselectivities for the corresponding cyclopropanes 5c , 5h , and 5i observed in these reactions were comparable to the results from the bulk-powder irradiations, and the yields improved when compared to their solution-phase counterparts. , These results demonstrate that the preparation and subsequent irradiation of suspended crystalline samples is an effective method to carry out highly selective solid-state photochemical reactions on synthetically useful scales.…”
Section: Resultsmentioning
confidence: 99%
“…Thermal reaction of trans-8 aa (Scheme 6, Figure S4): A benzene-d 6 (1.0 mL) solution of (3aZ,5Z,11R*,11aS*)-11-phenyl-1,3,11,11atetrahydrobenzo [4,5]cycloocta[1,2-c]furan-4-carbonitrile (trans-8 aa, 3.0 mg, 0.010 mmol) was placed in a NMR test tube. The solution was degassed by argon bubbling for 5 min and then the NMR test tube was sealed.…”
Section: Isolationmentioning
confidence: 99%
“…The significance of photochemistry in synthesis is increasing more and more these days. [1][2][3][4] Among them, photocycloaddition reactions between arenes and unsaturated bonds have been extensively studied not only from synthetic points of view but also from mechanistic aspects. [5][6][7][8][9][10][11][12] Photocycloaddition reactions between naphthalene rings and alkenes are known to have five modes as shown in Scheme 1.…”
Section: Introductionmentioning
confidence: 99%
“…Cooperative metal–photoswitch (M−Φ) “friendship” is an application-driven concept that bridges cutting-edge research from the materials science and physical, inorganic, and organic chemistry communities. Like good friends, metals (M) and stimuli-responsive organic molecules (e.g., photoswitches, Φ) possess individual strengths that can be synergistically combined to advance the behavior of both entities. For instance, M−Φ cooperation facilitates the development of stimuli-responsive homogeneous catalysts, while synergy of fast photoisomerization kinetics and M−Φ alignment in crystalline scaffolds is crucial to advance light harvesting. These are only a few examples among a large span of applications ranging from optically gated memory devices and quantum-computing systems to photodynamic therapeutic agents. , …”
Section: Introductionmentioning
confidence: 99%